Small eigenvalues of large Hankel matrices: The indeterminate case - Berg, Christian; Chen, Yang; Ismail, Mourad E. H. (MATHEMATICA SCANDINAVICA, 2002)
In this paper we characterize the indeterminate case by the eigenvalues of the Hankel matrices being bounded below by a strictly positive constant. An explicit lower bound is given in terms of the orthonormal polynomials and we find expressions for this lower bound in a number of indeterminate moment problems.